THE TECHNIQUE OF STABILIZED ACCOUNTING. - Sweeney, Henry W. (The Accounting Review, 1935)
This article attempts to describe the essence of stabilized-accounting procedure as the writer has developed it from the rather rudimentary stage in which it was left at the termination of the inflation period in Europe. The stabilizing procedure is based upon the index of the general price level. Stabilized accounting, by its use of price index numbers, estimates the reproductive or replacement costs of merchandise and fixed assets as at any dates for which reliable indexes are available. Stabilized accounting treats common stock and other investments in a business by its equity owners as real-value items, stabilizing them by the general index in order to show the current equivalents of the general purchasing power originally invested. When the accounts of a concern are stabilized, such restatement of capital stock does not mean, of course, that any stock records need be altered in any way. Stabilization on the basis of both original cost and reproductive-cost is shown in order to indicate how the two differ from each other and from accounting figures prepared from the books in the regular way.